The use of insect cells to identify potent and selective inhibitors of the replication of the Dengue and Chikungunya viruses and unravel their molecular mechanism of action (2015)
Dengue and Chikungunya viruses cause the most important arthropod-borne viral infections for humans. These viruses are predominant in tropical and subtropical regions. In addition, these viruses are predominant in tropical and subtropical regions. Dengue mortality rate is around 1.2 to 3.5% and deaths due to chikungunya fever are around 1 in 1000; however, half of chikungunya-infected patients evolve into a chronic state that can persist for months up to years. There are no antiviral drugs available for DENV and CHIKV treatment and prevention. Moreover, vector control strategies have failed so far. Thus, the development of potent inhibitors for a broad spectrum of RNA viruses is urgently needed. We established and characterized a new embryonic insect cell line from Culex quinquefasciatus mosquito. Also we established the flaviviruses and alphavirus replication, both in C6/36 and Lulo insect cell lines, as well as in Vero cell line. In addition we carried out a reference compound library and reference panel of assays and data for DENV, which provides a benchmark for further studies. During this study, a panel of 9 antiviral molecules, with proven in vitro anti-dengue virus activity and that act at different stages of the DENV life cycle, was selected. Finally, Favipiravir or T-705, was identified as inhibitor in vitro and in vivo of alphaviruses and the mutation K291R in nsP4, which is responsible of the polymerase activity, was found as the mode of action in CHIKV. Interestingly, lysine in motif F1 is also highly conserved in positive-stranded RNA viruses and this might explain the broad spectrum of T-705 antiviral activity.